DEVELOPMENT OF BUSSINES MODEL IN SENTULFRESH AGROTOURISM SERVICES - Zahid, Rifqi Az; Suroso, Arif Imam; Hannan, Sufrin (Jurnal Aplikasi Manajemen, 2020)
Knowing the problems and circumstances in a company is needed in the face of business competition, it can be the basis of strategic decision making for the company. Sentulfresh Indonesia has agrotourism products that offer educational activities on the theme of education on animals, plants, and biotechnology. As a new educational tourist attraction, Sentulfresh has the potential of natural resources and market potential that can be developed. This research uses the Business Model Canvas method to identify its business elements and then a SWOT analysis is performed on all existing BMC elements to form the basis of the future BMC idea by using the four-step framework from Blue Ocean Strategy. The results of this study indicate that the business model being undertaken needs some improvement and changes to be able to face the existing competition. Starting from the development of Key activities, namely the manufacturing of hydroponic plants will create a new and attractive value proposition as well as a new educational tourism market with broader customer segments as well as more diverse of the revenue stream. While the development of a value proposition in the form of batik activities will expand the market reach to junior and senior high school levels, even the adult community and generate new revenue streams without adding to the promotion costs for the two innovations above. This research still has many limitations, in terms of research objects there are still many that can be examined such as standardization of educational tourism, service quality, customer satisfaction, cost analysis etc. In terms of methodology, researchers can then combine BMC with other business methods in the Blue Ocean Strategy Book.